KAJIAN POLA ASUH ANAK PADA ISTERI NELAYAN DI KELURAHAN BERBAS PANTAI KECAMATAN BONTANG SELATAN KOTA BONTANG - Maya Anggraini; Elly Purnamasari; Oon Darmansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
This study aimed to describe the characteristics of the fisherman's wife who works and does not work, knowing parenting fishermen families in the Village Berbas Pantai. Research conducted at the Village Berbas Pantai District of Bontang Selatan, Bontang.Samples were fisherman's wife who works and does not work in the public sector with the criteria of having children aged 0-18 years as many as 66 people. Retrieving data using census method were analyzed by using descriptive and presented in narrative form, tables, and percentages.The results showed fisherman's wife age range 18-62 years, mostly aged 30-33 years (21.21%) and mostly just graduated from elementary school (56.06%). with the largest tribal groups are Bugis (69.61%). Most of the fisherman's wife did not work (60.60%). Type and parenting (procreation) either work or not work is the same. Parenting meal, respondents generally the exclusive breast feeding to infants 1 month - 2,5 years, after not depend on mother's milk feeding is done every child is hungry or crying percentage (95.45%) and only (4.54%) at the time certain. If their child is sick there is also brought to the clinic or doctor's clinic. Child respondents had education from early childhood / kindergarten (6:06%) to graduate SMA / SMK (15.15%) according to their age. Type parenting applied by the fisherman's wife is the type of democratic decision-making husband and wife to act democratically against children in order to get a good upbringing of the family.